2016
DOI: 10.1002/ijc.30500
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lu‐177‐trastuzumab for radioimmunotherapy of HER2 expressing breast cancer and its feasibility assessment in breast cancer patients

Abstract: HER2/neu is over expressed in 20-25% of breast cancers. HER2 breast cancers are aggressive and are associated with poor prognosis. The aim of this study was to develop the clinical grade Lu-177-trastuzumab and its preliminary evaluation for specific tumor targeting in HER2 positive breast cancer patients. Trastuzumab was conjugated to bifunctional chelator, DOTA, and characterized for integrity and the number of molecules conjugated. Radiolabeling of DOTA-conjugated trastuzumab was optimized using Lu-177. Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 25 publications
5
69
2
5
Order By: Relevance
“…A pilot study evaluated the feasibility of treating HER2+ mBC patients refractory to previous therapies with radioimmunotherapy developed by attaching the radioactive lutetium-177 (Lu-177) to trastuzumab. This study showed that the treatment was feasible and safe and could be considered for palliative treatment of HER2+ mBC in combination with standard agents [132].…”
Section: Enhancing the Her2-block Immune-mediated Mechanismmentioning
confidence: 99%
“…A pilot study evaluated the feasibility of treating HER2+ mBC patients refractory to previous therapies with radioimmunotherapy developed by attaching the radioactive lutetium-177 (Lu-177) to trastuzumab. This study showed that the treatment was feasible and safe and could be considered for palliative treatment of HER2+ mBC in combination with standard agents [132].…”
Section: Enhancing the Her2-block Immune-mediated Mechanismmentioning
confidence: 99%
“…This antibody has been labeled with 177 Lu, 64 Cu, 111 In,Thorium-227 ( 227 Th), Rhenium-188 ( 188 Re), Yttrium-90 ( 90 Y), and Iodine-131 ( 131 I). 34 37,45,63 66…”
Section: Targeting Of Her2 For Radionuclide Therapymentioning
confidence: 99%
“…Bhusari and coworkers developed a 177 Lu-trastuzumab tracer for radioimmunotherapy of HER2 expressing breast cancer and also explored its potential as an imaging agent. 53 This study demonstrated that the development, characterization and radiolabeling of 177 Lu-trastuzumab can be efficiently achieved in-house and that this radiotracer is safe to be administered to the patients. The HER2 positive primary and metastatic breast lesions specifically take up 177 Lu-trastuzumab, with two patient examples shown in Figures 7 (Day 1 and Day 7 time points) and Figure 8 (Day 5).…”
Section: Pet and Spect Imaging With Monoclonal Antibodies In Her2-posmentioning
confidence: 80%